Subcutaneous Pleomorphic Adenoma in an Accessory Parotid Gland in the Cheek - Kenko Aoki, MD; Mamiko Tosa, MD, PhD; Gou Akiyama, MD, PhD; Rei Ogawa, MD, PhD, FACs (Plastic and Reconstructive Surgery, Global Open)
Summary:. The accessory parotid gland (APG) is a distinct salivary tissue in the cheek that is located on the masseter muscle and is separate from the main parotid gland. APG tumors (APGTs) are rare. Due to aesthetic reasons and the risk of both malignancy and recurrence, APGTs are best treated with surgical resection. The resection should be conducted carefully due to potential complications such as Stensen duct and facial nerve injuries. Notably, plastic surgeons rarely see APGT cases because they are classified as parotid gland tumors and are thus mostly treated by otorhinolaryngologists. Nonetheless, because they are subcutaneous tumors in the cheek, patients with APGTs do occasionally visit the plastic surgery outpatient clinic. We report a case of APGT in a 59-year-old woman. She presented in our hospital with a rigid mass in the right cheek that was difficult to diagnose on the basis of clinical findings. After magnetic resonance imaging, APGT was considered along with several other possibilities. However, it was only diagnosed after histopathology on the resected tissues. Thus, plastic surgeons treating subcutaneous tumors of the cheek should consider APGT in their differential diagnosis and seek an accurate preoperative diagnosis, because this will help avoid postoperative complications.